Tales From the fringe : the representation of people with disabilities in contemporary Philippine children´s literature - Garces-Bacsal, Rhoda Myra; Hernández, Jesús Federico (Universidad Autónoma Metropolitana, Unidad Azcapotzalco, División de Ciencias Sociales y Humanidades, Departamento de Humanidades, 2014)
1 archivo PDF (11 páginas)